Effectiveness of Natural Products—Artemisia dubia and Manure Digestate—On Winter Wheat Cultivation - Ausra Baksinskaite; Modupe Olufemi Doyeni; Jurate Ramanauskienė; Dalia Feizienė; Vita Tilvikiene (Plants)
To effectively contribute to climate change mitigation, agronomists are increasingly focused on minimizing the application of synthetic fertilizers and pesticides while ensuring that crop yield and quality are not compromised. Plant biomass and organic fertilizers are known to improve soil quality, boost plant growth, and suppress diseases. However, their overall effectiveness remains limited, hence the need for further research to enhance their agricultural performance. This study aims to explore the potential application of two natural sources (manure digestate and crop Artemisia dubia) for crop fertilization and protection. During the growing season, winter wheat was fertilized twice (21–25 BBCH and 30–35 BBCH) with synthetic, organic (pig manure digestate), and combined synthetic–organic fertilizers. Artemisia dubia biomass was incorporated before sowing and planted in strips. The soil chemical composition, crop overwintering, weediness, and diseases were assessed after two years of the respective treatments. The results showed that the organic carbon content increased by 1–5% after fertilizing winter wheat with pig manure digestate and combining fertilizers (organic and synthetic). Additionally, fertilizer or pesticide use had a significant effect on the soil pH process. Combining synthetic and organic fertilizers increased the amount of mobile phosphorus in the soil by 38%. In conclusion, combining synthetic fertilizers with organic fertilizers is the most effective approach to maintain healthy soil conditions and prevent damage to sprouts in the soil. Overall, our findings offer more opportunities for organic and sustainable agricultural processes by integrating pig manure digestate and Artemisia dubia biomass as a natural approach to minimizing synthetic fertilizer and pesticide use.